Deformation microstructures in rocks - Mukherjee, Soumyajit (Springer Geochemistry/Mineralogy, 2013)
Study of microstructures is an indispensable component of understanding structural geology of any terrain. A number of 'new' microscopic structures such as 'flanking microstructures', trapezoid-shaped mineral grains, reversal of ductile shear sense, micro-duplexes, V-pull aparts, and new minerals nucleating inside host minerals have recently been described in individual manuscripts. However, for the sake of brevity, microstructural papers cannot show all possible variation in their morphology. The proposed book aims to present these structures with attractive colour photographs. Each photomicrograph will have a comprehensive caption. The book also presents grain boundary migration, boudins, symptoms of metamorphic retrogression, and how well known shear sense indicators (S-C fabrics, mineral fish etc.) vary in morphology in serial-sections. The target audience is for graduate and postgraduate geosciences students and researchers of structural geology.